The Quality of Communication and Depression Levels among Elderly Residents in Nursing Homes - Setyoadi, Setyoadi; Setyorini, Ika; Irmayanti , Ni Kadek Ayu Depy; Ismail, Dina Dewi Sartika Lestari (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2024)
Nursing home residents are more likely to experience symptoms of depression compared to seniors living at home. Older individuals face various physical and psychological challenges, such as hearing loss, vision impairment, and memory decline, which can hinder effective communication and diminish their overall well-being. This study aims to investigate the link between the quality of communication among older people in nursing homes and their levels of depression. The study uses observational analytics with a cross-sectional approach. The sample comprises 50 older individuals living in nursing homes, selected through purposive sampling. The independent variable is communication quality, evaluated using the Quality of Communication (QOC) questionnaire, while the dependent variable is depression level, assessed using the Geriatric Depression Scale (GDS) questionnaire. Data analysis involves calculating the Spearman Rank Correlation Coefficient at a 95% confidence level. The research findings show that 60% of the older participants exhibited moderate communication quality, while 88% experienced mild depression. The Spearman Rho statistical test resulted in a p-value of 0.009 and a correlation coefficient of -0.366, indicating a significant inverse relationship between communication quality and depression among older people. Nurses are encouraged to promote communication among nursing home residents by organizing activity groups, facilitating interactions, and creating environments conducive to social engagement. In conclusion, effective communication plays a crucial role in lowering the depression levels of nursing home residents.